Structural and electrical properties of excess PbO doped Pb(Zr0.52Ti0.48)O-3 thin films using rf magnetron sputtering method - Kim, TS; Kim, DJ; Lee, JK; Jung, HJ (MATERIALS RESEARCH SOCIETY, 1998)
Well-crystallized Pb(Zr0.52Ti0.48)O-3 thin films (4000 Angstrom thickness) can be synthesized on Pt/Ti/SiO2/Si(100) substrate at a temperature as low as 520 degrees C. The polycrystalline lead zirconate titanate (PZT) perovskite phase formation was confirmed with x-ray diffraction (XRD) analysis, and growth morphologies were studied with a scanning electron microscope (SEM). The electrical properties of PZT thin films were characterized through P-E hysteresis curve, dielectric constant, and loss, fatigue, and leakage current measurements. Remanent polarization (P-r) and coercive field (E-c) of as-grown film were 8-30 mu C/cm(2) and 24-64 kV/cm with the variation of applied voltage (5-15 V). The post-annealing enhances the electrical properties even at 500 degrees C, which is below the as-grown temperatures (520 degrees C). The average polarization loss after applying rectangular pulse (Vp-p = 10 V) up to 10(11) cycles was 40.9% for a 300 mu m small dot and 22% for a 500 mu m large dot, which are relatively improved values for platinum electrode. The values of dielectric constant (epsilon') and tan delta measured with small signal sign wave (1 V, 10 kHz) were 1207 and 0.066 in the case of as-grown film.